Changing educational aspirations of children living in poverty in Ethiopia - Tafere, Y (Young Lives, 2010)
Using both qualitative and quantitative data, this paper examines the changing educational and occupational aspirations and educational achievements of children living in poor communities in Ethiopia. The results suggest that children had high aspirations at an earlier age but that these changed later, with poverty rarely influencing their earlier aspirations but having a strong impact later on. Children with high educational achievement, mostly urban children and some rural girls, maintained their high ambitions. Education policy imposed constraints and provided varied opportunities for rural and urban children that affected their educational achievement and aspirations. Educational achievement was influenced by age of entry to school and continued attendance. Government development programmes and agricultural livelihoods attracted rural children’s labour and thereby negatively affected their education and realisation of their ambitions. The longitudinal data suggest that some children have begun considering out-of-school transitions (e.g. girls’ early marriage and full-time work for girls and boys) and, as a consequence, it seems that very few poor children will be able to realise their ambitions.